Management Talenta dalam Menghadapi Transformasi Agile Beurocratic di Ppsdm Aparatur - Maliani, Ani (JURNAL APARATUR, 2023)
AbstractProper management of human resource personnel is the precursor to realizing a superior work organization. Through the mandate of the Minister of State Apparatus Empowerment Regulation number 3 of 2020 concerning talent management, it is required that bureaucratic institutions have a talent pool.The research results show that the development category dominates PPSDM Apparatus employees: 16 people, 13 stars, and 10 misfits—solid contributor 3 people, concern 2 people, and promotable 1 person.The data above shows the need to properly handle competency development so that the human resource development function in PPSDM Apparatus can be carried out well. Proper preparation of human resources for personnel is in line with the transformation of government institutions towards bureaucratic agility, ready to face internal and external challenges. AbstrakPengelolaan SDM aparatur yang tepat menjadi cikal bakal hadirnya organisasi dengan kinerja superior. Melalui amanat peraturan menteri pendayagunaan aparatur negara dan reformasi birokrasi nomor 3 tahun 2020 tentang manajemen talenta, menuntut lembaga birokrasi memiliki talent pool. Berdasarkan hasil penelitian menunjukan pegawai didominasi oleh kategori development 16 orang, star 13 orang, Misfit 10 orang, solid contributor 3 orang, concern 2 orang dan promotable 1 orang. Dari data diatas menunjukan perlunya penanganan pengembangan kompetensi yang tepat agar fungsi pengembangan Sumber daya manusia di PPSDM Aparatur dapat terselenggara dengan baik. Penyiapan SDM apratur yang tepat selaras dengan transformasi lembaga pemerintah menuju agile beurocratic siap menghadapi tantangan baik internal maupun eksternal.